Desarrollo turístico de la Cascada Pan de Azúcar y el análisis de sus atributos naturales - Espinoza Gavilanes, Keyko Bosje (2021)
The present work of case study is directed to the tourist development of the Pan de Azúcar waterfalls, Ecuador has a great tourist potential with numerous areas that stands out for its natural and cultural biodiversity, in the province of Bolívar, Huamayacu is located 9 kilometers of the Caluma canton, where they have biodiversity of natural resources from waterfalls, fruit plantations such as orange, naranjilla, silk banana, chontilla, among others. The Canton Caluma has areas suitable for agriculture and livestock typical of the sierra region as well as the coast, due to its subtropical climate. The importance of this case study is to make the public aware of the current situation of this natural resource in order to establish the tourist development of the Pan de Azúcar Waterfalls and in this way give a better perspective of the resource to the owners of the sector, since by Through these proposed proposals, it is intended to improve tourist accommodation so that it is completely pleasant and comfortable for tourists. The purpose of this study is to analyze the natural attributes of the waterfall to gather information that will contribute to the dissemination of the particularities of the area, the results obtained and their analysis allowed to identify weaknesses such as the lack of promotion, support from the corresponding authorities and the lack of an adequate path. Among its strengths, its wonderful natural resource and fauna stand out. It is recommended to the owners and Municipal GAD to carry out a project for the better development of the Pan de Azúcar waterfalls.